2020
DOI: 10.3390/molecules25173912
|View full text |Cite
|
Sign up to set email alerts
|

Strong Positive Correlation between TSH and Ghrelin in Euthyroid Non-Growth Hormone-Deficient Children with Short Stature

Abstract: The growth processes in children depend on the proper functioning of some hormones and growth factors. Recently, a positive correlation between ghrelin and TSH (thyroid stimulating hormone) in patients with hyper- and hypothyroidism was proved. Moreover, in hypothyroid rats with high ghrelin concentration, growth hormone (GH) and insulin-like growth factor I (IGF-I) secretion was suppressed. We analyzed these relationships in euthyroid prepubertal children with idiopathic short stature (ISS). The analysis comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…However, this relationship does not only apply to persons with hyper or hypothyroidism and does not have to be related only to the patient's metabolic state. Accordingly, a strong positive correlation between ghrelin and TSH was observed in euthyroid children with normal body mass and idiopathic (non-GH deficit) short stature [124]. Moreover, it was confirmed that the higher ghrelin and TSH were, the lower nocturnal GH secretion and lower the IGF-1 were.…”
Section: Influence Of Tsh and Ft4 On The Ghrelin-gh-igf-1 Axismentioning
confidence: 68%
See 2 more Smart Citations
“…However, this relationship does not only apply to persons with hyper or hypothyroidism and does not have to be related only to the patient's metabolic state. Accordingly, a strong positive correlation between ghrelin and TSH was observed in euthyroid children with normal body mass and idiopathic (non-GH deficit) short stature [124]. Moreover, it was confirmed that the higher ghrelin and TSH were, the lower nocturnal GH secretion and lower the IGF-1 were.…”
Section: Influence Of Tsh and Ft4 On The Ghrelin-gh-igf-1 Axismentioning
confidence: 68%
“…Moreover, it was confirmed that the higher ghrelin and TSH were, the lower nocturnal GH secretion and lower the IGF-1 were. However, this observation was without any impact on FT4 concentrations [124]. Ghrelin receptors were found on human thyrocytes; the indirect suppression effect of ghrelin on thyrocytes was documented by Barington et al, in 2017 [125].…”
Section: Influence Of Tsh and Ft4 On The Ghrelin-gh-igf-1 Axismentioning
confidence: 94%
See 1 more Smart Citation
“…ere are many factors that cause the disease. Growth hormone (GH) deficiency, hypothyroidism, idiopathic shortness, intrauterine growth retardation, and IGF deficiency are the five main causes of short stature in children [3][4][5][6]. In addition to the disease that can cause children with short stature, children may be accompanied by mental and psychological disorders, introverted personality, lack of cognition, activity, and social skills [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between fasting and ghrelin, whose concentration correlates positively with TSH concentration, is well known. It is highly probable because the hormonal profile observed in the study group (increased TSH concentration during infection with no impact on FT4 concentration) is characteristic for the activity of ghrelin, whose elevated concentration directly inhibits T4 synthesis [31,32].…”
Section: Discussionmentioning
confidence: 99%